1998
DOI: 10.1111/j.1600-0722.1998.tb02204.x
|View full text |Cite
|
Sign up to set email alerts
|

SEM and EDS analysis of calcospherites in human teeth

Abstract: The present study was designed to characterize the morphology and composition of calco pherites in the coronal and root predentin of human permanent teeth by scanning electron microscopy (SEM) and scanning electron microscopy energy dispersive spectroscopy (SEM-EDS). Human inci ors. premolar ·. and molars were used. The ca lcospherites in the coronal predentin were globular and I 0 20 {Lm in diameter. The ca lcospherite · in the root predentin were smaller and their shape was different. Polygonal calcospherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…However, the influence of other ions is not so well defined. Among the ions detected in this study, Sr was thought to play a role in tooth mineralization 6,25) . In a recently published study, it was reported that Sr had the capacity to enhance enamel remineralization when used in conjunction with F 26) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of other ions is not so well defined. Among the ions detected in this study, Sr was thought to play a role in tooth mineralization 6,25) . In a recently published study, it was reported that Sr had the capacity to enhance enamel remineralization when used in conjunction with F 26) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of ion release from S-PRG filler is not completely understood, it is believed that the presence of a glass ionomer phase around the glass core of the filler is related to the ion release. Among the ions detected in this study, Sr is considered to play an important role in tooth mineralization 26,27) . A recently published study reported that Sr enhances enamel remineralization when used in conjunction with fluoride 28) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the ions released from S-PRG filler, Sr is thought to play a role in tooth mineralization. 28 The effect of Sr on enamel remineralization was previously investigated, and it appeared to have the capacity to enhance enamel remineralization in conjunction with F. 29 Si is thought to promote hydroxyapatite formation, as hydroxyapatite nucleation has been shown to be triggered in the presence of silica gel. 30 Hydrated silica gel has sufficient silanol groups to induce apatite nucleation on its own surface; nucleation then proceeds by taking Ca and P from the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%